PROSPECÇÃO HIDROGEOLÓGICA NO NÚCLEO URBANO DE REDENÇÃO - ARAÚJO, PAULO PONTES; MARQUES, VALTER JOSÉ; DREWS, MICHAEL GUSTAV PETER; COSTA, EXPEDITO JORGE DE SOUZA; VILLAS BOAS, JOSÉ MOURA; SERFATY, SUELY; SERFATY, ABRAHAM (Águas Subterrâneas, 1994)
RESUMO NÃO DISPONÍVEL